The Value of Insulin Resistance indices For detecting Insulin Resistance in Polycystic Ovarian Syndrome Patients - Gayathri, Dr.B.; Sweety S, T.Dixit; Aishwarya, S.; .P, Dr.Renuka; Vinodhini, Dr.V.M.; Anuradha, Dr.M. (International Journal of Life Science and Pharma Research, 2022)
Polycystic Ovarian Syndrome (PCOS) is characterized by increased ovarian and androgen hormone secretion. Patients with PCOS are said to be at high risk for insulin resistance(IR). IR is a sign of PCOS that comprises impaired glucose tolerance and elevated insulin production. HOMA-IR is a test that assesses insulin resistance by measuring blood glucose and insulin levels. There are other indexes that are also available for determining IR such as the quantitative insulin sensitivity check index(QUICKI) and McAuley index. Hence, in this study HOMA-IR, QUICKI and McAuley index were used to determine the IR among PCOS individuals. This case-control cross sectional study included 62 participants between the age group of 20-40 years. They were divided into two groups such as Group B which includes 31 PCOS patients diagnosed based on Rotterdam criteria and Group A includes 31 healthy age-matched female participants. After obtaining informed consent, fasting blood sample was collected from all the participants. Based on the analyzed biochemical parameters IR was assessed using HOMA-IR, QUICKI and McAuley index. For statistical analysis student t-test, ROC curve and bivariate regression analysis were done. In this study, it is observed that an increase in BMI was at a higher risk of developing PCOS. It is seen that fasting glucose, insulin and lipid profile (except HDL-C) were significantly elevated in PCOS individuals. The HOMA-IR was significantly increased and QUICKI and McAuley’s index were significantly decreased in PCOS which shows that PCOS patients are at higher risk of developing IR. Crude odds were calculated which shows that increase in HOMA-IR levels has an 86.25% increase risk of developing IR in PCOS patients when compared with the other indexes.HOMA-IR has a higher predictor % of developing IR in PCOS individuals, but still QUICKI and McAuley index can also be used as a predictor of risk.